2016
DOI: 10.1021/acs.jpcc.6b07437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Stratified Morphology of Nanoparticle Agglomerates

Abstract: Nanoparticles surrounded by gas agglomerate in a hierarchical fashion. From production until powder processing in the gas phase, nanoparticles go from individual particles to aggregates, simple agglomerates, and complex agglomerates. Even though the structures at each level have unique properties, they are commonly assessed as a whole. Additionally, the effect of external factors on the morphology of these structures during gas processing is not well understood and challenging to study due to the limited techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…It is reported that the density of simple agglomerates of ~40 μm is about 137 kg/m 3 . [ 16 ] This is reasonable considering the existence of more pores among the aggregates inside simple agglomerates with increasing size. The total porosity of the FNPAs ε a can be calculated by Equation ) from the two hierarchical porosities obtained.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…It is reported that the density of simple agglomerates of ~40 μm is about 137 kg/m 3 . [ 16 ] This is reasonable considering the existence of more pores among the aggregates inside simple agglomerates with increasing size. The total porosity of the FNPAs ε a can be calculated by Equation ) from the two hierarchical porosities obtained.…”
Section: Resultsmentioning
confidence: 83%
“…This is a typical three‐level hierarchical structure first revealed by Yao et al [ 5 ] and broadly accepted by many authors. [ 9,15,16 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations